2019
DOI: 10.20870/oeno-one.2019.53.3.2329
|View full text |Cite
|
Sign up to set email alerts
|

Climate change is implicating a two-fold impact on air temperature increase in the ripening period under the conditions of the Luxembourgish grapegrowing region

Abstract: Aim: Grape (Vitis vinifera L.) phenology is mainly temperature-driven. Consequently, the shift in thermal conditions due to climate change is supposed to have a distinct influence on grape phenology, grape maturity and wine typicity. This study aims to investigate (i) the future phenological development, as well as (ii) the consequences on the temperature conditions in specific phenophases under the conditions of the Luxembourg grapegrowing region.Methods and Results: A budburst model and a phenological model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 44 publications
1
36
1
1
Order By: Relevance
“…Similar trends are observed in many winegrowing regions around the world [45]. Advanced budbreak may expose vines more frequently to spring frost, although this risk depends on the climatic situation of each specific winegrowing region [49][50][51]. Phenology varies widely among varieties [52,53], with varieties selected historically to perform best in a given winegrowing region based on their phenology [3].…”
Section: Temperature Effectsmentioning
confidence: 76%
See 1 more Smart Citation
“…Similar trends are observed in many winegrowing regions around the world [45]. Advanced budbreak may expose vines more frequently to spring frost, although this risk depends on the climatic situation of each specific winegrowing region [49][50][51]. Phenology varies widely among varieties [52,53], with varieties selected historically to perform best in a given winegrowing region based on their phenology [3].…”
Section: Temperature Effectsmentioning
confidence: 76%
“…Higher temperatures advance grapevine phenology [46]. Hence, grapes ripen earlier in the season under warmer temperatures [49]. When grapes achieve full ripeness in the warmest part of the season (July-August in the Northern Hemisphere, January-February in the Southern Hemisphere) grape composition can be unbalanced (e.g., high sugar levels and low acidity), with red grapes containing less anthocyanins [59,60].…”
Section: Adaptations To Higher Temperaturesmentioning
confidence: 99%
“…Consequently, even if the grape health status allowed for a further potential delay in the harvest date, grapes in SMPH might not ever reach full maturity in phenologically late vintages and/or in the event of high/excessive crop load (as observed in 2013 where the legal minimum TSS levels for wines of protected designation of origin were not reached by any of the non-thinned SMPH treatments). However, (i) the more moderate yield levels with ongoing temporal distance to the transfer from VSP to SMPH and (ii) the potential temporal buffer for a continuation of the maturation period after the harvest period of the traditional VSP due to climate change (earlier start of the maturation period [19]; temporal prolongation of the potential vegetation period in autumn [20]), are supposed to compensate for the delayed maturation.…”
Section: General Behaviour Of Non-thinned Smphmentioning
confidence: 99%
“…Climate change projections are afflicted by uncertainties caused by mainly three factors: natural variability, model uncertainty, and greenhouse gas (GHG) emission scenario uncertainty [24]. Even though uncertainties in climate change projections exist depending on the underlying greenhouse gas emission scenarios, an annual air temperature increase of approximately 2.6 • C is projected for the region of investigation in the far future (2061-2090) compared to the reference period 1971-2000 [19].…”
Section: Smph As a Climate Change Adaptation Strategymentioning
confidence: 99%
“…Over a number of years, observations of wine producing regions have shown that temperature changes have modified vine development and the fruit maturation pattern Molitor & Junk (2019). Dates for grapevine bud break, flowering, and fruit maturation are now earlier than in the past.…”
Section: Rt Naude Mj Naudementioning
confidence: 99%